Identification and functional characterization of de novo variant in the SYNGAP1 gene causing intellectual disability - Li, Boxuan; Wang, Yu; Hou, Dong; Song, Zhen; Zhang, Lihua; Li, Na; Yang, Ruifang; Sun, Ping (Frontiers in Genetics, 2023)
Background: Intellectual disability (ID) is defined by cognitive and social adaptation defects.Variants in the SYNGAP1 gene, which encodes the brain-specific cytoplasmic protein SYNGAP1, are commonly associated with ID. The aim of this study was to identify novel SYNGAP1 gene variants in Chinese individuals with ID and evaluate the pathogenicity of the detected variants.Methods: Whole exome sequencing (WES) was performed on 113 patients diagnosed with ID. In the study, two de novo variants in SYNGAP1 were identified. Sanger sequencing was used to confirm these variants. Minigene assays were used to verify whether the de novo intronic variant in SYNGAP1 influenced the normal splicing of mRNA.Results: Two de novo heterozygous pathogenic variants in SYNGAP1, c.333del and c.664-2A>G, were identified in two ID patients separately. The c.333del variant has been reported previously as a de novo finding in a child with ID, while the c.664-2A>G variant was novel de novo intronic variant, which has not been reported in the literature. Functional studies showed that c.664-2A>G could cause aberrant splicing, resulting in exon 7 skipping and a 16bp deletion within exon 7.We identified two de novo pathogenic heterozygous variants in SYNGAP1 in two patients with ID, among which the c.664-2A>G variant was a novel de novo pathogenic variant.Our findings further enrich the variant spectrum of the SYNGAP1 gene and provide a research basis for the genetic diagnosis of ID.